Local human capital, segregation by skill, and skill-specific employment growth - Friso Schlitte (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
Labour markets in most highly developed countries are marked by rising levels of skill segregation in the production process and increasing inequalities in skill-specific employment prospects. The local skill structure is frequently regarded as a major cause for regional growth disparities. There are several studies investigating the influence of the local human capital endowment on qualification-specific wages levels. Furthermore, theoretical studies suggest that skill segregation might matter for the polarisation of wages and employment. However, analyses on regional employment growth by different skill levels are still scarce and empirical evidence on the effects of skill segregation on qualification-specific employment is completely lacking. This paper investigates the effects of the local skill composition and skill segregation in the production process on qualification-specific employment growth in West German regions. This study provides first evidence for negative effects of skill segregation on low-skilled employment growth. Furthermore, the results show that a large share of local high-skilled employment does not foster further regional concentration of human capital but positively affects the employment prospects of less skilled workers.
Keywords: R11; J21; J24; 330; regional employment growth; low-skilled employment; skill segregation